Optoelectronic application of colloidal quantum dots in infrared beyond Si (invited) - Hwang, Gyu Weon; Junyoung Jin; Taehwan park; JEONG TAE HOON (239th ECS Meeting and the 18th International Meeting on Chemical Sensors (IMCS), 2021)
Among electromagnetic wave spectrum, infrared region has many attractive applications such as a LiDAR, optical communication, telecommunications, thermography, bioimaging, photovoltaics, and night visions. However, the expensive cost of epitaxial III-V semiconductors and the fabrication process hinders the widespread of the infrared technology beyond the silicon absorption range. Colloidal quantum dots have a great potential as an alternative materials for infrared detection. Lead chalcogenide QDs not only have tunable bandgap in infrared region but also have process compatibility with conventional Si ROIC in the device fabrication process, which remarkably reduces fabrication costs. The performance of photodetectors incorporating the lead chalcogenide QDs, however, is suboptimal and needs further improvement. One of the main factors limiting the performance of QD-based photodetectors is a high density of surface defects. QDs inherently have large surface-to-volume ratios and dangling bonds on the surface acted as trap sites. Various methods to reduce surface defects, such as thermal and ligand treatment, have been introduced; however, even after these treatments, QD-based photodetectors still show the relatively low detectivity (D*).
Keywords: QD; SWIR